Waiting times and equilibrium selection - Beggs, A (University of Oxford, 2003)
This paper shows how graphs can be used to calculate expected waiting times in models of equilibrium selection. It also shows how reducing the state space can simplify the calculations both of waiting times and selected equilibria. The results are applied to potential games and games with strategic complementarities.